Strength behaviors of undisturbed Malan loess under rainfall leaching in Yan’an area, China - Xie, Qingyu; Huang, Qiangbing; liu, Yue; Wang, Zhuangzhuang; Yu, Daijin; Peng, Jianbing (Bulletin of engineering geology and the environment, 2023)
Understanding the impact of rainfall leaching on the shear strength of loess is critical for evaluating loess slope stability. In this study, the effect of rainfall leaching on the shear behavior and microstructure of loess was analyzed via rainfall leaching, triaxial shear, grain size distribution, and mercury intrusion porosimetry tests to determine the mechanisms of strength degradation in undisturbed Malan loess under rainfall leaching. The analyses show that the shear failure mode of undisturbed loess depends on the confining pressure and the amount of rainfall leaching. Under low confining pressure, the strain-softening phenomenon gradually disappears with the increases of rainfall leaching. Affected by rainfall leaching, the cohesion decreases significantly until residual value, and the internal friction angle decreases slightly; this effect is closely related to particle cementation. Through microstructure analysis, the undisturbed loess remains well-graded after being subject to different rainfall leaching; the seepage force generated by rainfall leaching causes the cemented material between particles to soften, move, and disintegrate, resulting in pore collapse and a decrease in total porosity. Macropores and mesopores are more active due to the influence of cementation materials, which are easy to loess collapse during rainfall leaching. Moreover, according to the numerical model of fluid–structure coupling, revealing that with increased rainfall leaching, the maximum plasticity strain value of the slope toe increased rapidly. Under the same rainfall leaching conditions, the stability of loess slope decreases with the increase of slope angle.